Magic Forms and The Mathematical Creative Thinking Ability of Secondary School Students - Muntazhimah, Muntazhimah (Universitas Wiralodra, 2023)
A growing body of literature has shown that mathematics learning is expected to facilitate students to develop creative thinking abilities. In reality, students' creative thinking abilities are not fully accommodated through mathematics learning. Therefore, this research aims to explore middle school students' mathematical creative thinking abilities based on learning experiences with Magic Forms. This qualitative research with an explorative approach focuses on the participation of three class VII students at a state junior high school in Jakarta (MA, LS, and YC). Data collection techniques used in this study were learning outcomes tests and interviews. Data analysis techniques in this study used data reduction, data presentation, and drawing conclusions. Based on the results of the study, it was found that: MA meets the four indicators of mathematical creative thinking ability, MA felt helped by the experience of learning with Magic Forms and challenged by the experience of working on the ability to think creatively. LS met the four indicators of mathematical creative thinking ability, LS also felt helped by the experience of learning with Magic Forms and amazed by the experience of working on the ability to think creatively. YC met the four indicators of mathematical creative thinking ability, for the subject's authenticity indicator reached a percentage of 68.75% (higher indicator). Moreover, YC did not feel helped by the experience of learning with Magic Forms and was confused by the experience of working on the ability to think creatively.